PENGARUH ELECTRONIC WORD OF MOUTH DAN KREDIBILITAS INFLUENCER DI INSTAGRAM TERHADAP CUSTOMER PURCHASE INTENTION - Michell Wijaya Koesuma; Kurniawati Kurniawati (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Advances internet technology and social media have driven the industry forward and have changed the way products and services are marketed. Social media platforms have become the focus of businesses that define marketing strategies. Instagram is one of the most attractive social media sites today. Aim: Analyzing the positive influence of e-WOM quality, e-WOM quantity, influencer credibility in Instagram and brand trust on customer purchase intention either directly or indirectly with the mediating variable of brand trust. Research Methodology: The analysis of each research variable was carried out using SPSS version 25 with a mean value. Analysis of the influence between variables, both directly and indirectly, was carried out using Structural Equation Marketing (SEM). Data was collected from 300 respondents who have Instagram and have knowledge of the Luxcrime, Makeover, and Wardah brands, as well as influencers. Result: The quality of e-WOM and influencer credibility do not have a positive effect on customer purchase intention. The quantity of e-WOM and brand trust has a positive effect on customer purchase intention. Influencer credibility has a positive effect on brand trust. Brand trust partially mediates the relationship between influencer credibility and customer purchase intention. Managerial Implications: This research is used as an evaluation material for the managerial brands of Luxcrime, Makeover, and Wardah in maintaining and improving the quality of e-WOM, quantity of e-WOM, influencer credibility, brand trust, and customer purchase intention.